The effect of galsulfase enzyme replacement therapy on the growth of patients with mucopolysaccharidosis VI (Maroteaux-Lamy syndrome) - Harmatz, P.; Hendriksz, C.J.; Lampe, C.; McGill, J.J.; Parini, R.; Leão-Teles, E.; Valayannopoulos, V.; Cole, T.J.; Matousek, R.; Graham, S.; Guffon, N.; Quartel, A. (Molecular genetics and metabolism, 2017)
Mucopolysaccharidosis (MPS) VI is an autosomal recessive lysosomal storage disorder arising from deficient activity of N-acetylgalactosamine-4-sulfatase (arylsulfatase B) and subsequent intracellular accumulation of the glycosaminoglycans (GAGs) dermatan sulfate and chondroitin-4-sulfate. Manifestations are multi-systemic and include skeletal abnormalities such as dysostosis multiplex and short stature. Reference height-for-age growth charts for treatment-naïve MPS VI patients have been published for both the slowly and rapidly progressing populations. Categorization of disease progression for these charts was based on urinary GAG (uGAG) level; high (>200μg/mg creatinine) levels identified subjects as rapidly progressing. Height data for 141 patients who began galsulfase treatment by the age of 18years were collected and stratified by baseline uGAG level and age at ERT initiation in 3-year increments. The reference MPS VI growth charts were used to calculate change in Z-score from pre-treatment baseline to last follow-up. Among patients with high baseline uGAG levels, galsulfase ERT was associated with an increase in Z-score for those beginning treatment at 0–3, >3–6, >6–9, >9–12, and >12–15years of age (p<0.05). Increases in Z-score were not detected for patients who began treatment between 15 and 18years of age, nor for patients with low (≤200μg/mg creatinine) baseline uGAG levels, regardless of age at treatment initiation. The largest positive deviation from untreated reference populations was seen in the high uGAG excretion groups who began treatment by 6years of age, suggesting an age- and severity-dependent impact of galsulfase ERT on growth. •Growth of galsulfase-treated patients was evaluated relative to natural history.•Galsulfase had an age- and severity-dependent impact on growth.•Severely affected patients grew more even when initiating ERT as late as 12–15years.•The largest growth benefit was seen in severely affected patients starting ERT by 6years.